Synthesis and properties of the bio-based isomeric benzoxazine resins: Revealing the effect of the neglected short alkyl substituents. (15th August 2021) - Liu, Jingkai; Wuliu, Yishun; Dai, Jinyue; Hu, Jingyuan; Liu, Xiaoqing
Graphical abstract: Highlights: Two high purity bio-based isomeric benzoxazine resins are synthesized. The benzoxazine isomers shows different crystallization efficiency and crystals. Distinct cross-linking networks and H-bonds are obseved in cured resins. The leverage of short-chain alkyl groups on benzoxazine chemistry is revealed. Abstract: Bio-based feedstocks usually contain many isomers with similar structures, and the short alkyl substituents are generally considered as low-reactive groups in benzoxazine chemistry due to their low induction effect and chemical inertness. Therefore, little attention has been paid on their effects on the synthesis or properties of benzoxazine. In this work, two bio-based benzoxazine isomers (CAR-fbz and THY-fbz) containing methyl and isopropyl groups with interchanged positions were synthesized from the renewable carvacrol and thymol. Their synthetic process, crystal features, and curing reactions were carefully investigated. Results showed that different side reacitions and by-products were detected under the same synthese conditions. And using the similar purification method, CAR-fbz and THY-fbz with high purity were found to have different crystal features. In addition, the cured systems also indicated varied H-bonding features and thermal properties based on differential scanning calorimetric (DSC) and thermogravimetric analysis (TGA) results. With the help of density functional theory (DFT) calculation, the reasons were attributed to the different electrophilicity of phenol moiety, varied molecular symmetry and intermolecular interaction caused by the overlooked short alkyls. Summarily, the leverage of short-chain alkyl groups on benzoxazine chemistry is revealed. The result is significant for the benzoxazine synthesis, especially when the renewable compounds are taken as the starting materials for bio-based benzoxazine preparation, which often has many isomers with similar structures.